Observation of Γ-Valley Moiré Bands and Emergent Hexagonal Lattice in Twisted Transition Metal Dichalcogenides - Ding Pei; Binbin Wang; Zishu Zhou; Zhihai He; Liheng An; Shanmei He; Cheng Chen; Yiwei Li; Liyang Wei; Aiji Liang; Jose Avila; Pavel Dudin; et al. (Physical Review X, 2022)
Twisted van der Waals heterostructures have recently been proposed as a condensed-matter platform for realizing controllable quantum models due to the low-energy moiré bands with specific charge distributions moiré superlattices. Here, combining angle-resolved photoemission spectroscopy with submicron spatial resolution (μ-ARPES) and scanning tunneling microscopy (STM), we performed a systematic investigation on the electronic structure of 5.1° twisted bilayer WSe_{2} that hosts correlated insulating and zero-resistance states. Interestingly, contrary to one’s expectation, moiré bands were observed only at Γ valley but not K valley in μ-ARPES measurements, and correspondingly, our STM measurements clearly identified the real-space honeycomb- and kagome-shaped charge distributions at the moiré length scale associated with the Γ-valley moiré bands. These results not only reveal the unusual valley-dependent moiré-modified electronic structure in twisted transition metal dichalcogenides, but also highlight the Γ-valley moiré bands as a promising platform for exploring strongly correlated physics in emergent honeycomb and kagome lattices at different energy scales.